The Histomorphometry of Liver and Kidney of Hyperglycemic Albino Rats after Treatment with Tithonia diversifolia Leaf Extract - Rizki Fitrawan Yuneldi; Tyas Rini Saraswati; Enny Yusuf Wachidah Yuniwarti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Tithonia diversifolia can be used as an antidiabetic, so it is necessary to study the safety of its use, especially the side effects on the liver and kidneys. This study aimed to determine the effect of using T. diversifolia leaf extract through histomorphometry observations of the liver and kidneys of hyperglycemic albino rats. The study design used a completely randomized design (CRD). This study used 20 male albino rats which were divided into five treatment groups, there were T0 (rat normal/control), T1 (hyperglycemic rat without T. diversifolia leaf extract), T2 (hyperglycemic rat administered with Glibenclamide 10 mg/kg BW), T3 (hyperglycemic rat administered with T. diversifolia leaf extract 150 mg/kg BW), T4 (hyperglycemic rat administered with T. diversifolia leaf extract 300 mg/kg BW). Every treatment was repeated four times. The damage of hepatocyte and the glomerular cell was observed through histological structure observation by histomorphometry method using a photomicrography microscope (Olympus BX51). The results indicate that there were significant differences (P 0.05) in the variable of hepatocytes diameter and there was no significant different (P 0.05) result on glomerular diameter, as well as kidney and liver weight. It was concluded that T. diversifolia leaf extract of 150 mg/kg BW and 300 mg/kg BW are safe to be used as antidiabetic. It does not cause any side effects on the liver and kidneys of hyperglycemic albino rats. Thereby T. diversifolia leaf extract can be further tested as preparation of biopharmaca which can be used as herbal medicines for diabetics.